Artificial Intelligence: GEN Z Auditing Students of Universitas Advent Indonesia - Sinaga, Judith Gallena; Siagian, Valentine; Chaniago, Ria (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2025)
This study explores the relationship between Gen Z auditing students and artificial intelligence (AI), focusing on their competencies, awareness, and frequency of AI tool usage. Utilizing a qualitative research method, questionnaires were distributed to 50 auditing students at Universitas Advent Indonesia through Google Forms. The instrument was designed around four key perspectives: AI competencies, most used AI tools, level of AI awareness, and frequency of AI use in academic tasks. Respondents were selected using purposive sampling to ensure relevance, with ethical standards upheld through voluntary participation and data confidentiality. Findings reveal that while auditing students frequently use AI tools—particularly ChatGPT for tasks like communication, brainstorming, report writing, and presentation creation—their overall AI competence remains moderate, and their awareness tends to be surface-level, focusing more on tool usage than on understanding underlying principles or ethical implications. This highlights a clear gap between usage and mastery. As the future of the auditing profession becomes increasingly intertwined with AI, it is essential to enhance students’ digital literacy and critical understanding of AI’s capabilities and limitations. The study concludes that while Gen Z auditing students are technologically engaged, targeted educational interventions and curriculum development are needed to ensure their future relevance and leadership in a digitally evolving accounting profession.